2015
DOI: 10.1186/s12958-015-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Difference in expression between AQP1 and AQP5 in porcine endometrium and myometrium in response to steroid hormones, oxytocin, arachidonic acid, forskolin and cAMP during the mid-luteal phase of the estrous cycle and luteolysis

Abstract: BackgroundRecently, we demonstrated in vitro that AQP1 and AQP5 in the porcine uterus are regulated by steroid hormones (P4, E2), arachidonic acid (AA), forskolin (FSK) and cAMP during the estrous cycle. However, the potential of the porcine separated uterine tissues, the endometrium and myometrium, to express these AQPs remains unknown. Thus, in this study, the responses of AQP1 and AQP5 to P4, E2 oxytocin (OT), AA, FSK and cAMP in the porcine endometrium and myometrium were examined during the mid-luteal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Our experiments confirmed the AQP1 and AQP5 gene expression in the porcine uterine luminal epithelial cells [11,[25][26][27], a novel finding was that AQP2 and AQP7 are also expressed in these cells. In addition, in this study, we investigated the effects of the estradiol, progesterone, arachidonic acid, H89 (selective PKA inhibitor), and PD98059 (MAPK inhibitor) on the AQP1, AQP2, AQP5, and AQP7 gene expression in the uterine epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our experiments confirmed the AQP1 and AQP5 gene expression in the porcine uterine luminal epithelial cells [11,[25][26][27], a novel finding was that AQP2 and AQP7 are also expressed in these cells. In addition, in this study, we investigated the effects of the estradiol, progesterone, arachidonic acid, H89 (selective PKA inhibitor), and PD98059 (MAPK inhibitor) on the AQP1, AQP2, AQP5, and AQP7 gene expression in the uterine epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…In the transcellular pathway, aquaporins are mainly responsible for a large amount of transport of water, which is driven by the osmotic gradient [6]. It has been already shown that several factors, including hormones, regulate uterine transepithelial water transport via modulating the expression level of AQPs [6,[25][26][27]40]. As shown in our results, treatment with steroid hormones (E 2 and P 4 ) resulted in a predominantly stimulatory effect on AQP1 and AQP2 mRNA expression.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…They stimulate follicular cell proliferation and, together with FSH, initiate the formation of LH receptors in granulosa cells, mainly in the mural, progesterone and androgen production in theca interna cells [ 37 , 38 ]. A thorough discussion regarding the influence of steroid hormones on aquaporins in the female reproductive system has been already presented in our previous papers [ 39 , 40 , 41 ]. In turn, very interesting results on transgenic mice deficient in AQP proteins showed different reproductive phenomena in both males and females [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that these secreted miRNAs could also modulate the maternal intrauterine environment. To the best of our knowledge, this is the first study examining miRNA expression profiles in the culture media harvested after exposure of different segments of the sow genital tract (explants from uterus, UTJ and isthmus) to SP (from SRF, post-SRF and EE) for 16 h. Oviduct and uterine explants have been cultured from several mammalian species (including pigs), and widely used as a standardized model to evaluate in vitro female genital tract responses to different treatments, due to the fact that the epithelium is exposed, as in the in vivo situation [ 44 , 45 , 46 , 47 , 48 ]. Although this ex vivo model may not completely reflect the changes that could take place in vivo, it provides reliable and useful data that can contribute to a better understanding about the role played by SP on the secretion of miRNAs by female genital tract.…”
Section: Discussionmentioning
confidence: 99%